Faktor Budaya Sekolah, Lingkungan Kerja dan Kepuasan Kerja Kontribusinya pada Kinerja Guru (Studi Kasus Guru SMP Negeri di Kecamatan Juli Kabupaten Bireuen) - Muchlisin, Muchlisin; A. Rahman, Aisyah (peusangan, 2024)
The issue of performance is very interesting and continues to be studied academically. Because there are many factors that support it. In this regard, this study took a case study on a sample of 62 junior high school teachers in Juli sub-district, Bireuen district, Aceh province, which still has many obstacles. The study was conducted by surveying with interviews and questionnaires using associative quantitative methods with statistical analysis tools, namely the path model. The results found that: 1). The level of teacher performance is not optimal, assessed in the moderate category, namely 78.4% of ideal expectations. 2) factors of organizational culture, work environment and job satisfaction contribute to teacher performance, the results of the analysis obtained each influence of 42.14 percent, 50.36% and 67.1%. 3) Simultaneously, organizational culture, work environment and job satisfaction contribute to teacher behavior in their performance by 59.2%. As a note also, there is causality between factors of organizational culture, work environment and job satisfaction with an average at a fairly strong level.